Penyetaraan Jabatan Administrasi ke dalam Jabatan Fungsional Bagi Aparatur Sipil Negara Perspektif Fiqh Siyasah - Liza Yuliana; John Kenedi; Ismail Jalili (CV. Doki Course and Training, 2024)
The purpose of this study is to examine the problem of equalizing administrative positions into functional positions for state civil servants at the State Islamic University of Bengkulu from the perspective of